Determinants of Tax Revenues and Human Development Index in Indonesia - Lestari, Fibria Anggraini Puji; Yolanda, Yolanda (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research is motivated by curiosity about the relationship between taxation and the Human Development Index.Taxes are one of the most important sources of government revenue for development financing, one of which is human development. The purpose of this study is to find out the extent of the relationship between taxation and the human development index. The samples used came from 30 provinces in Indonesia The method used in this study was quantitative descriptive analysis. Secondary data from 1991 to 2021 were used and analyzed using the Eviews application 12 The results of the study concluded that variables such as interest rates, tax ratios, working-age population, and exports affect tax revenues both in the short and long term